Governor Edmund G. Brown Jr. California Delegation Caucus (1976)
This document outlines the rules for the California Delegation Caucus supporting Governor Edmund G. Brown Jr., held on June 26, 1976. The caucus was open to registered Democrats and the press, but only publicly elected delegates (or their replacements) could vote for at-large delegates and alternates. Nominations required petitions signed by at least 15% of eligible voters, voting was by open written ballot, and participants had to vote for a fixed number of candidates without cumulative voting. Similar procedures applied to alternates and to recommendations for party committee positions, and nominees could withdraw at any time before or during voting. The rules also prohibited campaign materials in the caucus hall and authorized the chair to appoint volunteers to oversee and administer the proceedings.